Monitoring the Domestic Harvest of Migratory Birds in Nunatsiavut, Labrador - Natcher, David C.; Felt, Larry; Chaulk, Keith; Procter, Andrea; Government, Nunatsiavut (ARCTIC, 2011)
The 2007 Nunatsiavut Inuit Migratory Bird Harvest Study found that the harvest of migratory birds by Nunatsiavut (Labrador) communities represents an important component of their overall subsistence harvest. During the 2006 – 07 year, the Nunatsiavut migratory bird harvest was a reported 5468 birds. Annual harvest estimates at the household, community, and regional levels are summarized. Although these data represent only a single harvesting year, the baseline information that has now been identified will contribute to the establishment of Inuit domestic harvest levels, thereby recognizing the legitimate harvesting needs of Inuit households, while helping to ensure the conservation of migratory bird populations into the future. L’étude Nunatsiavut Inuit de 2007 portant sur les oiseaux migratoires a permis de constater que la récolte des oiseaux migrateurs par les collectivités du Nunatsiavut (Labrador) représente une composante importante de la récolte de subsistance générale de ces collectivités. Au cours de l’année 2006-2007, la récolte des oiseaux migratoires du Nunatsiavut s’est chiffrée à 5 468 oiseaux. Cet article résume les récoltes estimées par domicile, par collectivité et par région. Bien que les données ne représentent qu’une seule année de récolte, l’information de base qui en a été tirée aidera à déterminer les taux de récolte domestiques des Inuits, ce qui permettra de faire ressortir les besoins légitimes en récolte des foyers inuits tout en favorisant la conservation des populations d’oiseaux migrateurs à l’avenir.